Stimulation of ROS Generation by Extract of Warburgia ugandensis Leading to G0/G1 Cell Cycle Arrest and Antiproliferation in A549 Cells - Yong-Li Zhang; Gui-Lin Chen; Ye Liu; Xiao-Cui Zhuang; Ming-Quan Guo (MDPI AG, 2021)
Warburgia ugandensis Sprague (WU) is a traditional medicinal plant used for the treatment of various diseases, including cancer, in Africa. This study aimed to evaluate the anti-non-small cell lung cancer (NSCLC) activities of WU against A549 cells and to reveal potential molecular mechanisms. The cytotoxicity of various WU extracts was evaluated with HeLa (cervical cancer), HepG2 (liver cancer), HT-29 (colorectal cancer), and A549 (non-small cell lung cancer) cells by means of Sulforhodamine B (SRB) assay. Therein, the dimethyl carbonate extract of WU (WUD) was tested with the most potent anti-proliferative activity against the four cancer cell lines, and its effects on cell viability, cell cycle progression, DNA damage, intracellular reactive oxygen species (ROS), and expression levels of G0/G1-related proteins in A549 cells were further examined. First, it was found that WUD inhibited the proliferation of A549 cells in a time- and dose-dependent manner. In addition, WUD induced G0/G1 phase arrest and modulated the expression of G0/G1 phase-associated proteins Cyclin D1, Cyclin E1, and P27 in A549 cells. Furthermore, WUD increased the protein abundance of P27 by inhibiting FOXO3A/SKP2 axis-mediated protein degradation and also significantly induced the γH2AX expression and intracellular ROS generation of A549 cells. It was also found that the inhibitory effect of WUD on the proliferation and G0/G1 cell cycle progression of A549 cells could be attenuated by NAC, a ROS scavenger. On the other hand, phytochemical analysis of WUD with UPLC-QTOF-MS/MS indicated 10 sesquiterpenoid compounds. In conclusion, WUD exhibited remarkable anti-proliferative effects on A549 cells by improving the intracellular ROS level and by subsequently modulating the cell proliferation and G0/G1 cell cycle progression of A549 cells. These findings proved the good therapeutic potential of WU for the treatment of NSCLC.